Breast Cancer, a Heterogeneous Disease Entity The Very Early Stages - Kahán, Zsuzsanna; Tot, Tibor (Springer Netherlands : Imprint: Springer, 2011)
The volume raises attention to the need of a completely new approach to breast cancer based on the knowledge collected on early breast cancer in the past two decades. The chapters are contributed by experts of all the fields participating in the clinical research and care of breast cancer. The practical importance of such a book is underlined by the increasing number of breast cancer cases, and also the increasing proportion of early stage-cases. The ultimate goal of the book is to point to the heterogeneous nature of the disease which is more striking and has more importance in care at the very early stages than at the more advanced stages. The book recommends the utilisation of all the information provided by multimodality imaging and special pathological methods, a new classification system and therapeutic guidelines since early breast cancers should not be treated based on experience obtained with palpable tumors. No similar book has been yet released to the market. The book is written for all the members of the team participating in the diagnosis and treatment of breast cancer (radiologists, pathologists, surgeons, clinical and radiation oncologists), but may be useful for medical students and residents too. The chapters are illustrated with didactic pictures, and special emphasis is given to provide a peep into the practice of the special procedures for the careful examination and individualized therapy of each case.